Investigating the effects of marantodes pumilum leaves aqueous extract on uterine contractility in post-partum rats / Wan Fatein Nabeila Wan Omar - Wan Fatein Nabeila, Wan Omar (2016)
Marantodes pumilum (MP) or locally known as Kacip Fatimah is a herbal plant found mainly in South East Asia. Despite its traditional use by the Malay women for postpartum uterine involution, there is no study performed to investigate the effects of this herb on uterine contractility in the post-partum period. The aims of this study were therefore to investigate the effects of M. pumilum on post-partum uterine contractility and the underlying mechanisms involved. Methods: This study was performed in postpartum SD female rats (n=24). Aqueous extract of M. pumilum var Alata was administered orally for seven consecutive days at 100, 250 or 500 mg/kg/day. At day 8 post-delivery, the rats were humanely sacrificed and uteri were subjected for ex-vivo contractility study to determine the force of contraction with the remaining tissue harvested for protein expression by Western blotting and immunostaining. Blood was collected for reproductive hormone analyses. Results: Our findings indicated a significant increase in the force of uterine contraction (p<0.05) in rats receiving 500 mg/kg/day of M. pumilum when compared to control. In these rats, progesterone levels were decreased with higher expression of contractile proteins (MLCK, SERCA, and CaM), calcium signaling proteins (JP3K, Ga and GP), uterotonic receptors (Muscarinic M2 receptor, PGF2a receptor and Oxytocin receptor) and estrogen receptors in the myometrium. Conclusions: M. pumilum increases uterus contractility in the postpartum period via inducing an increase in expression level of contractile proteins in the myometrium as well as increase in signaling pathways that lead to uterine contraction. Additionally, this herb decreases progesterone level which increases contractility of the uterus. Therefore, M. pumilum is potentially useful as a uterotonic agent to facilitate uterine involution after delivery.